Co-crystals of thiobarbituric acid and N-heterocyclic compounds: Synthesis, structural, solubility, computational, and antilymphoma activity - Nidhi Goel; Hem Lata; Dhananjay S. Raghubanshi; Shiv Govind Rawat; Ajay Kumar; Naresh Kumar (Next Materials)
Two new co-crystals (1–2) were prepared by the reaction of 2-thiobarbituric acid with N-heterocyclic compounds, and successfully characterized. X-ray analysis shows that 1 and 2 have zig-zag and ladder like supramolecular frameworks, respectively. HOMO-LUMO analysis of optimized geometries confirmed the lesser band gap of 1 and 2. Co-crystals 1–2 have solubility values of 19.737 and 25.652 mg/ml, respectively, and they may have good bioactivity. The cytotoxic activity of 1–2 indicated the tumor growth inhibitory ability of 1 and 2 against T cell lymphoma. Interestingly, apoptosis evaluation by Wright-Giemsa and DAPI staining suggested that 1 and 2 mediated tumor cell death through apoptosis induction. In addition, the estimation of glucose, pH, and NO also indicated the possible role of inhibited glucose uptake and augmented NO production in the cell death mediated by 1 and 2.